COVID-19 and the Indian healthcare scenario - Barman, Paramita (International Journal Of Community Medicine And Public Health, 2023)
Background: The Indian economy and health system has been shaken to the core by the sudden strike of the COVID-19 pandemic. The already fragile and underequipped public health system reeled under the pressure of escalating cases of infection and demand for hospitalization of critical and emergency cases of COVID. Although the private healthcare sector worked in sync with the public counterpart and provided adequate support for case management, the former is not expected to play the primary role when it comes to a public health crisis like COVID-19. The study attempts to explore the pattern of utilization of the existing health system by Indian households in the event of general illness, which is expected to throw some light on the mechanism for devising an optimal public-private mix for management of COVID or similar public health threats in future. Methods: The study was exploratory and based on secondary data. It employs unit level data from NFHS-4 (2015-16) besides published reports and documents. Results: Health insurance coverage is low among households belonging to the lowest wealth quintile. Inequalities in access to quality health care coupled with spiraling health costs due to COVID and falling incomes continue to push such vulnerable households into poverty and debt. Conclusions: Public expenditure on health should be increased with a shift in focus from curative to preventive care.